Peningkatan Jumlah Apoptosis Airway Smooth MuscleBerhubungan dengan Peningkatan + Jumlah Sel T CD8 pada Model Mencit Asma - Setiawati, Dessy; Kusuma, HMS Chandra; Kusworini, Kusworini (Fakultas Kedokteran Universitas Brawijaya, 2009)
Airway remodeling is an important thing in asthma.The increase of airway smooth muscle mass is a prominent feature of asthmatic airway remodeling. The importance role of airway smooth muscle cell (ASM) + apoptosis in airway remodeling is unknown.T cell also had important role in asthma, whereas CD4 T cell +role in airway remodeling has already known, but how CD8 T cell role in airway remodeling is still unclear. A randomized control group experimental study used Balb/c mice, that categorized into 2 groups: asthma and control. Asthma group was sensitized by ovalbumin intraperitoneally in day 0 and 14, followed by inhalation +every 2-3 days for 6 weeks. In week 8, all of mice were terminated. The expression of CD8 T cell lymphocyte was examined through immunohistochemistry method, whereas ASM apoptosis by TUNEL method. Independent sample t-test and spearman test was used in statistical analysis with confident interval 95%. The bronchioli and lungs specimens were obtained from 18 mice (9 in each group). Case goup had significant +increase in the amount of ASM apoptosis and expression of CD8 T cell lymphocyte (p=0.000; p=0.001). +There was also positif correlation between ASM apoptosis and expression of CD8 T cell (r=0.37, p=0.065). +We conclude that increasing ASM apoptosis has a relationship with increasing CD8 T cell+Keywords: asthma, mice, ovalbumin, ASM apoptosis and CD8 T cell